Ultimate guide to LinkedIn for business - Prodromou, Ted, ....- (Entrepreneur Media : [s.l.], 2015)
This popular title delivers an in-depth guide to targeting, reaching, and gaining ideal customers using the latest updates on LinkedIn. LinkedIn expert Ted Prodromou offers a wealth of no- or low-cost methods for maximizing this dynamic resource. Following his lead, readers learn to link with the most effective connections for greater exposure. Updates in this edition include: staying up-to-date with LinkedIn Contacts, Pulse, and Publisher programs; expansion of premium accounts to help optimize business profiles, stand out in search results, and track impact; how to implement new features like Showcase and Company Updates pages for extended presence in newsfeeds and with followers; smarter LinkedIn Search that saves time and money with customized, comprehensive results. Other important topics covered include: techniques and tips to easily navigate LinkedIns interface; timesaving tips on finding and matching data from businesses and people; expert guidance on super-charging a business or individual profile; insider advice on getting found through LinkedIn and maximizing search; professional instruction on promoting a LinkedIn profile. The latest information is illustrated with current snapshots, fresh examples, and case studies, along with new techniques to easily maneuver LinkedIns interface.
Keywords: LinkedIN